Determinism of Media Technology and Distortion of Siri’ Culture - Qadaruddin, Muhammad; Bakri, Wahyuddin; Md Shah, Jalihah; Cahyadi, Irlan; Sasriani, Andini (Communicatus: Jurnal Ilmu komunikasi, 2023)
The rapid development of communication technology, particularly in social media platforms such as Facebook, TikTok, and Instagram, profoundly influences the entire human experience. The influence includes cultural shifts among adolescents, precisely distortions to the "Siri" culture that affect their self-concept, self-esteem, and self-image. This qualitative research aimed to analyze changes in the Siri’ culture in communication among adolescents, the impact of communication media technology, and indicators of Siri' character building. The data was collected through observations, surveys, and interviews. The results showed two main findings: first, in the culture of adolescents in Parepare City, Siri’ is interpreted as a local philosophy that emphasizes the importance of maintaining self-respect in the daily style, speech, and behavior. It has a direct impact on the formation of adolescents' self-concept. The second, media technology has a significant influence on cultural changes and adolescents' self-concept (macca, lempu, warani, getting), self-esteem (penggalik), and self-image (malebbi, mekkeade, makanja).